Sepsis‐related anemia in a pediatric intensive care unit: transfusion‐associated outcomes. (5th March 2020) - Elshinawy, Mohamed; Kamal, Maha; Nazir, Hanan; Khater, Doaa; Hassan, Radwa; Elkinany, Hassan; Wali, Yasser
Abstract : BACKGROUND: Pediatric patients with sepsis in intensive care units are at high risk of developing anemia, which might have adverse effects on their prognosis. This study aimed to evaluate the impact of red blood cell (RBC) transfusion on the outcomes of patients admitted to a pediatric intensive care unit (PICU) with sepsis. METHODS: We conducted a prospective randomized clinical trial, enrolling 67 children, aged 2 to 144 months who were admitted to a PICU with a new episode of sepsis from November 2017 to April 2018. Patients were allocated randomly to two groups: Group 1, liberal transfusion strategy group, including 33 patients who had initial hemoglobin (Hb) between 7 or greater and less than 10 g/dL and received an RBC top‐up transfusion to 12 g/dL; and Group 2, restrictive strategy group, including 34 patients who had the same Hb range and did not receive RBCs. Patients with Hb less than 7 or greater than 10 g/dL were excluded. RESULTS: Of 33 patients who received liberal transfusions, 31 (93.94%) required ventilation, and 29 (87.88%) had multiorgan dysfunction. They had a significantly lengthier hospital stay and a higher incidence of acute respiratory distress syndrome and acute lung injury. Moreover, mortality was significantly higher in the liberal transfusion group (42.4% vs. 17.6%). CONCLUSIONS: Compared to the restrictive transfusion strategy, liberal transfusion might be associated with a worse outcome. However, the possible role of other known and unknown confounding factors and minor protocol violations should be taken into consideration. We recommend minimizing factors worsening anemia in PICU patients to reduce the need for transfusion.